2001
DOI: 10.1093/glycob/11.6.91r
|View full text |Cite
|
Sign up to set email alerts
|

Heparanases: endoglycosidases that degrade heparan sulfate proteoglycans

Abstract: Heparanases are endoglycosidases that cleave the heparan sulfate glycosaminoglycans from proteoglycan core proteins and degrade them to small oligosaccharides. Inside cells, these enzymes are important for the normal catabolism of heparan sulfate proteoglycans (HSPGs), generating glycosaminoglycan fragments that are then transported to lysosomes and completely degraded. When secreted, heparanases are thought to degrade basement membrane HSPGs at sites of injury or inflammation, allowing extravasion of immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
136
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 64 publications
0
136
0
1
Order By: Relevance
“…However, these heparan sulphate changes occur at the macroalbuminuric stage of diabetic nephropathy, since no glomerular heparan sulphate alterations were found at the microalbuminuric stage [15]. Recently, we showed that glomerular production of heparanase, an endo-β-1,4-D-glucuronidase involved in the hydrolytic cleavage of the β-1,4-glycosidic bond between glucuronic acid and glucosamine residues within N-sulphated and/or Nacetylated/N-sulphated domains of heparan sulphate [16,17], was increased in patients with overt diabetic nephropathy [11,18]. In addition, heparanase activity was detected in the urine of diabetic patients [19].…”
Section: Introductionmentioning
confidence: 94%
“…However, these heparan sulphate changes occur at the macroalbuminuric stage of diabetic nephropathy, since no glomerular heparan sulphate alterations were found at the microalbuminuric stage [15]. Recently, we showed that glomerular production of heparanase, an endo-β-1,4-D-glucuronidase involved in the hydrolytic cleavage of the β-1,4-glycosidic bond between glucuronic acid and glucosamine residues within N-sulphated and/or Nacetylated/N-sulphated domains of heparan sulphate [16,17], was increased in patients with overt diabetic nephropathy [11,18]. In addition, heparanase activity was detected in the urine of diabetic patients [19].…”
Section: Introductionmentioning
confidence: 94%
“…44). Heparanase can be present both at the cell surface and in intracellular endosomal compartments.…”
Section: Suramin Treatment Causes Accumulation Of S-nitrosylatedmentioning
confidence: 99%
“…Heparan sulfate (HS) 3 is a structurally complex polysaccharide that is expressed ubiquitously on the cell surface and in the extracellular matrix. HS is composed of repeating disaccharide units of glucuronic acid (GlcUA) and glucosamine.…”
mentioning
confidence: 99%